1997
DOI: 10.1076/ceyr.16.7.640.5058
|View full text |Cite
|
Sign up to set email alerts
|

Real-time confocal microscopic observations on human corneal nerves and wound healing after excimer laser photorefractive keratectomy

Abstract: TSCM clinically confirms the earlier histological data on healing of excimer laser wounds. It offers a distinct improvement in the assessment of excimer laser-treated corneas, as it enables cellular details and nerves to be perceived in vivo. In addition the thickness of the stromal scar can be be measured for e.g. planning of phototherapeutic keratectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0
5

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(51 citation statements)
references
References 22 publications
2
44
0
5
Order By: Relevance
“…The confocal microscopic features of the operated corneas were much the same as previously published by others (Corbett et al, 1996;Linna and Tervo, 1997;Mùller-Pedersen et al, 1997;Frueh, Cadez and Bo Èhnke, 1998;Bo Èhnke, Thaer and Schipper, 1998). The most interesting area to be viewed more closely was the subepithelial area with regenerating nerves and subepithelial haze.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…The confocal microscopic features of the operated corneas were much the same as previously published by others (Corbett et al, 1996;Linna and Tervo, 1997;Mùller-Pedersen et al, 1997;Frueh, Cadez and Bo Èhnke, 1998;Bo Èhnke, Thaer and Schipper, 1998). The most interesting area to be viewed more closely was the subepithelial area with regenerating nerves and subepithelial haze.…”
mentioning
confidence: 63%
“…The return of the keratocytes into quiescence takes months (Linna and Tervo, 1997;Bo Èhnke et al, 1988;Frueh et al, 1998), and the timing coincidences with the gradual disappearance of the subepithelial haze (as observed on slit lamp) and regeneration of the innervation. Mùller-Pedersen et al (1997) showed delicate subbasal nerve ®bers in nine out of 17 patients at 1 month after PRK, whereas according to Frueh et al (1998) only 1/18 corneas presented with subbasal nerves at that time.…”
mentioning
confidence: 87%
“…Differences have been noted between rabbits and humans in wound healing responses so caution must be exercised in extrapolating these data to humans. For example, there appears to be more regression and greater overall inflammatory response to LASIK in rabbits than in humans [21][22][23] . At the same time, Ambrosio and colleagues [24] concluded that the overall wound healing response in human eyes that had epithelial scrapes prior to enucleation for retinal or orbital tumors was very similar to that in rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…PRK'dan 1 hafta sonra subbazal sinirlerde rejenerasyon görülmeye başlandığı ve 8-12. haftada parsiyel ya da total iyileşme gözlendiği saptanmıştır. [36][37][38] Prospektif bir çalışmada ise miyopik PRK sonrası 2. yılda sinir yoğunluğunda %80 iyileşme görülmüş ve bu değerler 5 yıl süreyle stabil kalmıştır. 39 Ancak bazı olgularda PRK'dan 5 yıl sonra bile subbazal sinir morfolojisinin normal haline dönmediği görülmüştür.…”
Section: Kuru Gözde Kornea Sinir Değişiklikleri Ile Bulgu Ve Semptomlunclassified